Practicing core reflection : activities and lessons for teaching and learning from within / Frits G. Evelein, Fred A.J. Korthagen. - Evelein, Frits G. (Routledge, 2014)
Practicing Core Reflection features 78 concrete educational activities and exercises based on research. These can be used individually and in groups to support ''teaching and learning from within.' Core Reflection is an approach focused on people''s personal strengths and on using practical strategies to overcome obstacles to the enactment of these strengths. This approach has been used in many contexts all over the world and has shown great promise in helping to re-chart the course for education and to re-think its purpose in global and democratic societies. Additional tools (Cards, Figures,